Effect of Inhibitors of Aggregation on Platelet Ultrastructure in Vitro - Mannucci, P. M; Sirigu, F (Thrombosis and Haemostasis, 1969)
Electron microscopy observations are presented on the effect of inhibitors of aggregation on platelet morphology. Moreover the relationship existing between shape changes produced by inhibitors of platelet aggregation and the mechanism of inhibition has also been studied.Among the inhibitors, nucleotides were without effect on platelet shape, so that their inhibitory action is likely to be related to competition with ADP.Marked sphering of platelets with scanty modifications of the inner structure was produced by all other agents. They are thought to be active through a damage to the membrane, which is thus made insensitive to the aggregating agents.